The Importance of the Development of Literary Taste among Arabic Language Learners of Non-Arabic Speakers - Mat Daud, M.; Hj Abdul Manaf, M.F. (Universiti Sains Islam Malaysia, 2024)
Literature is the mirror of the nation and the lungs in which it breathes as literature describes the history of the nation and expresses its hopes, pains and ambitions. Literature possesses a prominent position in preparing the soul, shaping the personality and guiding of human behaviour in general. It is also a way to educate the conscience, purify the senses, and sharpen the mind. A nation that lacks literature lose its existence and history for literature is the root of civilization. Perhaps one of the most important goals of teaching literature is to familiarize students with the taste of literary texts, through which they learn about the beauty of artistic work in literary work, and embark on enhancing the literary taste, and stand upon the characteristics of aesthetic language. The importance of this study is to develop the levels of skills in stimulating literary taste by teachers, and for the students to learn literary texts through selected literary pieces to encourage them to enjoy the literature in which it is crucial for students to develop their emotional aspects. Therefore, it aims to raise the level of Arabic literature through deepening and embarking on the literary taste to recognise the aesthetic citizen and the methods of literary work.